Análise dos aspectos da abordagem CTSA no contexto de um clube de educação ambiental e tecnologias digitais - VALE, Junivon da Silva (Universidade Federal do Oeste do Pará, 2024)
The present aims to analyze how the implementation process and the practices developed in an Environmental Education and Digital Technologies Club contemplate aspects of the STSE approach. The research starts from the author's experience with the STSE approach during graduation, as well as the interest in studying aspects related to the environment, which was made possible by the experiences in the implementation of a Science Club. The implementation of the Club took place in a school in the rural area of the santareno plateau, in the west of Pará. As a data collection instrument, a logbook produced in the monitoring of the Club's activities was used, a Focus Group with members of the Club's coordination team, collaborators and scholarship holders of the FORMAZON Research Group belonging to the Federal University of Oeste do Pará. Data analysis was based on Yin's proposal (2016) composed of the steps: a) compile, b) decompose, c) recompose (and arrange), d) interpret, e) conclude. The results show the importance of the Club for the school and region in order to promote the strengthening of environmental education practices and scientific training. The strong articulation of the Club's implementation process and activities with the STSE approach was observed. The experiences were significant to promote improvements in the scientific training of students. In this sense, the Club has the potential to expand teaching activities by producing knowledge in connection with the school community (local and regional context), favoring scientific research integrated with the sociocultural values of the community and the goals of the school, that is, promoting environmental education and scientific, related to the aspects that make up the STSE approach.